(untitled) (Heritage, 2023)
The topic of this paper is biblical motifs in epic poems about Nemanjic dynasty. The holy dynasty of Nemanjic, during which Serbia experienced a cultural, economic, territorial and social flourishing, left anindelible mark in the Serbian collective memory. The influence of the Bible on folk epic literature is sostrong that it is impossible to understand and interpret this type of Serbian cultural heritage withoutknowing biblical motifs and symbols.